Computerintegrated technology for the early detection of breaches in the borehole walls stability in the drilling process - Golovata, Yulia; Kohutiak, Miroslav; Lagoyda, Andriy; Sabat, Natalya; Sementsov, George (Eastern-European Journal of Enterprise Technologies, 2017)
We substantiated and examined computer-integrated technology for the early detection of breaches in the stability of walls of a borehole based on the knowledge base of clear rules that allow operating the sets of input technological parameters and preventing emergencies. A formal mechanism is proposed for supporting the decision-making process in real time based on the operation with logic functions to detect breaches in the stability of walls of a borehole. This makes it possible to directly operate with the developed clear logic structure and information on the current values of controlled factors and to provide intelligent support for the process of decision-making when establishing governing values for the controlled parameters of a technological process. A basis of the devised formal mechanism is the model that is presented in the normal disjunctive form. It provides for a high level of analysis of the current input information and the formation of decision on the breach of stability of the walls of a borehole with the loss of circulation. We realized the scheme of logic device (finite automaton), designed for the early detection of breach in the stability of walls of a borehole in the process of drilling oil and gas boreholes, which is based on logic function and the Veitch-Karnaugh methods. The designed device, based on the current information about the factors of drilling process, generates optimal decision regarding early detection of breach in the stability of walls of a borehole.